2022
DOI: 10.1101/2022.01.04.475010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variable Shh and Fgf8 positioning in regenerating axolotl limb guarantees consistent limb morphogenesis in different limb sizes

Abstract: Limb regeneration in Ambystoma mexicanum occurs in various sizes of fields and can recreate consistent limb morphology. It was not known what mechanism supports such stable limb morphogenesis regardless of size. Limb regeneration in urodele amphibians has been basically considered to recapitulate the limb developmental processes. Many molecules in the limb developmental processes are conserved with other tetrapods. SHH and FGF8 play important roles in the morphogenesis of limbs among them. Focusing on these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Similar findings were reported using a hyperinnervation model of Xenopus froglet forelimb regeneration; Mitogawa et al (2018) demonstrated that increased limb innervation promotes blastema cell proliferation, and causes changes in pro‐regenerative gene expression and morphology mediated by fgf2/8 , bmp , and shh signaling 105 . Expression of fgf8 and shh have also been shown to regulate axolotl digit patterning, although the authors did not investigate whether neurons were involved 108 …”
Section: Nerves and Blastema‐mediated Regenerationsupporting
confidence: 52%
See 1 more Smart Citation
“…Similar findings were reported using a hyperinnervation model of Xenopus froglet forelimb regeneration; Mitogawa et al (2018) demonstrated that increased limb innervation promotes blastema cell proliferation, and causes changes in pro‐regenerative gene expression and morphology mediated by fgf2/8 , bmp , and shh signaling 105 . Expression of fgf8 and shh have also been shown to regulate axolotl digit patterning, although the authors did not investigate whether neurons were involved 108 …”
Section: Nerves and Blastema‐mediated Regenerationsupporting
confidence: 52%
“…105 Expression of fgf8 and shh have also been shown to regulate axolotl digit patterning, although the authors did not investigate whether neurons were involved. 108 There are several other soluble factors that have been implicated in nonmammalian blastema-mediated regeneration. Other growth factors include newt anterior gradient (nAG) protein 50,52 and neuregulin-1 (NRG1).…”
Section: Soluble Factor Signalingmentioning
confidence: 99%